Factors affecting the changes in antihypertensive medications in patients with hypertension - Chung, Tae Kyu; Jeon, Yoomin; Hong, YeSol; Hong, Suyeon; Moon, Jun Sik; Lee, Howard (Frontiers in Cardiovascular Medicine, 2022)
As frequent changes in anti-hypertensive (HTN) medications may reduce adherence to the treatments, identifying modifiable factors leading to changes in anti-HTN medications can help clinicians optimize treatment strategies for individual patients. We performed this study to explore the pattern of anti-HTN medications and to identify factors that are associated with the changes in anti-HTN medications. To this end, we used a clinical database of Seoul National University Hospital, extracted, transformed, and loaded by the observational medical outcomes partnership common data model. Demographic and all recorded clinical diagnoses, medications, and procedures data of eligible subjects were collected. Of 636 subjects who were eligible for this study, 297 subjects with a record of ≥1 anti-HTN medication changes and other 297 subjects without a record of medication change were selected for the study population. High diastolic blood pressure (adjusted odds ratio [OR]: 1.02, 95 % confidence interval [CI]: 1.001-1.040, p=0.040), arrhythmia (adjusted OR: 10.01, 95 % CI: 1.86-185.57, p=0.030), and angina pectoris with antianginal agents (adjusted OR: 4.85, CI: 1.05-23.89, p=0.046) were associated with the changes in anti-HTN medications, indicating that any patients with these covariates require additional attention to reduce the likelihood of changing anti-HTN medications.